Hydrogen and water bonding between glycosaminoglycans and phospholipids in the synovial fluid: Molecular dynamics study - Beldowski, Piotr; Mazurkiewicz, Adam; Topoliński, Tomasz; Małek, Tomasz (Materials, 2019)
Synovial fluid is a lubricant of the synovial joint that shows remarkable tribological properties. These properties originate in the synergy between its components, with two of its major components, glycosaminoglycans (GAGs) and phospholipids (PLs), playing a major role in boundary and mixed lubrication regimes. All-atom molecular dynamic simulations were performed to investigate the way these components bond. Hyaluronic acid (HA) and chondroitin sulphate (CS) bonding with three types of lipids was tested. The results show that both glycosaminoglycans bind lipids at a similar rate, except for 1,2-d-ipalmitoyl-sn-glycero-3-phosphoethanolamine lipids, which bind to chondroitin at a much higher rate than to hyaluronan. The results suggest that different synovial fluid lipids may play a different role when binding to both hyaluronan and chondroitin sulphate. The presented results may help in understanding a process of lubrication of articular cartilage at a nanoscale level.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Chondroitin sulphate; Hyaluronic acid; Hydrogen bond; Molecular dynamics simulation; Osteoarthritis; Phospholipids; Synovial fluid; Water bridges